Correlation between age, nationality and results of elite ski racers between 1982 and 2025 - Ivanova I.G. ,; Novikova N.B. ,; Beleva A.N. ,; Kotelevskaya N.B. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to investigate the relationship between the age and nationality of athletes and their performance at various distances in World Cups, World Championships and Olympic Games between 1982 and 2025 in order to identify current trends in the development of the sport. Methods and structure of the study. Data for the period 1982-2025 was downloaded from the International Ski Federation website and the ‘Statistics’ section for analysis. Results and conclusions. Trends have been identified indicating an increase in the average age of prize-winners among men from 1982 to 1999 and among women from 1982 to 1996, which reaches 29-30 years. There is also a forecast for a decrease in this indicator to 26-27 years by 2020, followed by an increase by 2025. The most noticeable changes are observed in middle-distance races for men and long-distance races for women. Until 2022, Russian athletes demonstrated the best results in pursuit races. The obtained research data can be used to improve the training system of ski racers in our country.